2021
DOI: 10.1007/s10578-021-01216-4
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Among Adolescents: Testing Vulnerability-Stress and Protective Models in the Context of COVID-19

Abstract: Adolescents who experience negative life events may be at risk for depression, particularly those with psychosocial vulnerabilities. We investigate longitudinally the impact of vulnerability/protective factors on the relation between a large-scale negative life event, the COVID-19 pandemic, and depressive symptoms. Adolescents (N = 228, M age = 14.5 years, 53% female, 73% white) self-reported depressive symptoms 2–4 months before the pandemic (Time 1), and again 2 months following stay-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…For the two studies used PHQ-9, Giannopoulou et al ( 27 ) reported statistically increased depression score in post COVID-19 period, with an SMD of 0.41 (95% CI: 0.28, 0.54), whereas for Andreas and Brunborg ( 30 ), the increase was insignificant (SMD: 0.05, 95% CI: −0.03, 0.13). The two studies used PHQ-8 all found higher depression score after COVID-19 pandemic, with SMDs of 0.28 (95% CI: 0.02, 0.54) for Jolliff et al ( 28 ) and 0.20 (95% CI: 0.01, 0.38) for Gladstone et al ( 31 ). The two studies used MFQ also yielded positive findings, with SMDs of 0.32 (95% CI: 0.18, 0.47) for Black et al ( 26 ) and 0.08 (95% CI: 0.02, 0.14) for Westrupp et al ( 33 ).…”
Section: Resultsmentioning
confidence: 96%
“…For the two studies used PHQ-9, Giannopoulou et al ( 27 ) reported statistically increased depression score in post COVID-19 period, with an SMD of 0.41 (95% CI: 0.28, 0.54), whereas for Andreas and Brunborg ( 30 ), the increase was insignificant (SMD: 0.05, 95% CI: −0.03, 0.13). The two studies used PHQ-8 all found higher depression score after COVID-19 pandemic, with SMDs of 0.28 (95% CI: 0.02, 0.54) for Jolliff et al ( 28 ) and 0.20 (95% CI: 0.01, 0.38) for Gladstone et al ( 31 ). The two studies used MFQ also yielded positive findings, with SMDs of 0.32 (95% CI: 0.18, 0.47) for Black et al ( 26 ) and 0.08 (95% CI: 0.02, 0.14) for Westrupp et al ( 33 ).…”
Section: Resultsmentioning
confidence: 96%
“…• social disadvantage [28,78] • living in an apartment, without access to green space [68] • female gender (general mental health problems, quality of life, attention problems, addictive behaviour) [28,37,47,90] • male gender (depression, anxiety, internalising symptoms, well-being, life satisfaction, stress, psychosomatic symptoms) [37,[59][60][61][62]68,70,80,83,93,95] • younger age (depression, anxiety, behavioural addiction) [27,32,58,66,79,93] • older age (internalising and externalising problems, quality of life) [28,35,37] • living in a house, access to green space [68] Intra-individual factors…”
Section: Factors Influencing Covid-19-related Changes In Mental Healthmentioning
confidence: 99%
“…• pre-existing mental health problems [62,76,83] • poor physical health [49] • neurodevelopmental disorders, special educational needs [35,37] • negative coping strategies (emotion-focussed engaged and disengaged coping) [41,63] • dysfunctional/missing emotion regulation abilities (e.g., dampening positive emotions) [29,54,70,74] • negative cognitive styles [59] • emotional instability [42] • high extraversion [43] • good physical health [49] • positive coping mechanisms (e.g., talking to friends, prioritising sleep, problem-focussed engaged coping)…”
Section: Factors Influencing Covid-19-related Changes In Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the pilot study took place during the COVID-19 pandemic, when the campus environment presented unique challenges for students with and without symptoms of depression and when rates of depression increased particularly for females (e.g., Chen et al 2020;Gladstone et al 2021;Magson et al 2021). Moreover, follow-up assessments for this pilot study were conducted when COVID-19 cases were decreasing and social distancing restrictions were being lifted.…”
Section: Overall Discussionmentioning
confidence: 99%